Smartphone nation : why we're all addicted to screens and what you can do about it - Regehr, Kaitlyn (London : Bluebird / Pan Macmillan, 2025)
"The compassionate, practical guide for raising--and becoming--healthy and informed digital citizens in the age of the smartphone, social media and AI. A must-read for parents of the smartphone generation. We know the dangers of consuming ultra-processed food. But what about the way algorithms are ultra-processing the information we consume online? How do today's parents, who grew up without digital devices and social media, parent a generation who are awash in it? Digital devices are everywhere in young people's lives--in their schools and in their homes, with their friends and when they're alone. But parents know there is increasing evidence about both the risks and harms associated with online content. This presents an urgent dilemma: a digital-free life isn't realistic, but how can parents keep the risks to their children at bay? How do they help their kids to manage their online activity (not to mention their own)? Some have argued that the only way forward is to disconnect and opt your kids out. But the discourse around banning phones is backwards looking. It's us as geriatric millennials and Gen X-ers nostalgically reminiscing about our Nokias and their supposed innocence. Whether you like it or not, your kids will need to be on the internet, and their lives and careers will be shaped by AI. And it's the kids that understand the harms of technology and know how to navigate them effectively that will thrive. They will be at the front of the line. Smartphone Nation marshals the evidence and gives parents simple takeaways for implementing healthy digital nutrition for their families. This isn't a digital detox book recommending that we throw away our digital devices. This is a book that understands the realities and pressures that parents face. Dr. Kaitlyn Regehr argues that knowledge is power, and that by understanding your own relationship with the internet, social media and AI, you will develop the tools you need to make choices for you and your family."--
This book examines the challenges of raising children in a digital environment shaped by smartphones, social media, and artificial intelligence. Regehr reviews research on the risks and impacts of online content, explores how algorithms influence information consumption, and outlines strategies for developing healthy digital habits within families. Framed as a practical guide for parents, the work emphasizes digital literacy, informed decision-making, and approaches to helping children navigate technology rather than avoid it.
Includes bibliographical references (pages 179-243).
Keywords: Digital media -- Social aspects; Digital media -- Safety measures; Internet and children; Internet -- Safety measures; Electronics -- Social aspects; Information society; Parenting; Internet -- Security measures; Smartphones -- Social aspects